Progress of research on PD-L1 inhibitor adebrelimab usage in malignant tumors - Cheng, Pan; He, Jichen; Cheng, Pingping; Chen, Kaixia; Zhao, Guangyu (Frontiers in Oncology, 2024)
Adebrelimab is a humanized monoclonal antibody against programmed death-ligand 1 (PD-L1) and is also a novel immune checkpoint inhibitor, which has been used in the first-line treatment of extensive stage small cell lung cancer (SCLC) with its unique mechanism of action and good clinical efficacy. Significant progress has been made in the treatment of adebrelimab in other malignancies such as non-small cell lung cancer, triple-negative breast cancer, esophageal squamous cell carcinoma, and the treatment of SCLC at different stages is also being explored. Therefore, adebrelimab emerges as a promising new treatment option for patients with small cell lung cancer (SCLC) and other types of malignant tumors.